2009
DOI: 10.4314/eamj.v86i4.46948
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette Smoking And Oral Health Among Healthcare Students

Abstract: Background:The knowledge, attitudes and practices of cigarette smoking and health risks among health workers has been found to be predictive of their efficiency as agents for tobacco cessation campaigns. Objective: To describe the knowledge, attitudes and practices of cigarette smoking and oral health risks among healthcare professional students. Design: A cross sectional multi-level study. Setting: College of Health Sciences, University of Nairobi. Subjects: Two hundred and eighty one students. Results: Thirt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
11
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 23 publications
4
11
2
Order By: Relevance
“…This is com parable to the results obtained by Komu et al, 5 in their study among healthcare students reported 62.5% commencing smoking before entering the university. Oladele et al 19 and Fawibe and Shittu 14 in their studies reported that over 80% of students started smoking before their 18th birthday, this coincided with their secondary school age.…”
supporting
confidence: 87%
See 4 more Smart Citations
“…This is com parable to the results obtained by Komu et al, 5 in their study among healthcare students reported 62.5% commencing smoking before entering the university. Oladele et al 19 and Fawibe and Shittu 14 in their studies reported that over 80% of students started smoking before their 18th birthday, this coincided with their secondary school age.…”
supporting
confidence: 87%
“…In developing countries, 7% of women and 48% of men smoke, the situation is different in developed countries, where 24% of women smoke as compared to 42% of men. 2 The effects of smoking on oral tissues include reduced taste perception, staining of teeth, palatal keratosis, melanosis, oral candidiasis, 5 halitosis and dental caries.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations